Bulk nanostructuring intermetallic composite material; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Ovcharenko V. E. Vladimir Efimovich; Psakhie S. G. Sergey Grigorievich; Ivanov Yu. F. Yuriy Fedorovich; Ivanov K. V.; Boyangin E. N. (2014, 2014)
Title screen